Case study: Reinforcement of 45S5 bioglass robocast scaffolds by HA/PCL nanocomposite coatings. (November 2017) - Motealleh, Azadeh; Eqtesadi, Siamak; Pajares, Antonia; Miranda, Pedro; Salamon, David; Castkova, Klara
Abstract: The purpose of this study is to analyze the mechanical enhancement provided by nanocomposite coatings deposited on robocast 45S5 bioglass (BG) scaffolds for bone tissue regeneration. In particular, a nanocomposite layer consisting of hydroxyapatite (HA) nanoparticles, as reinforcing phase, in a polycaprolactone (PCL) matrix was deposited onto the surface of the BG struts conforming the scaffold. Three different HA nanopowders were used in this study. The effect of particle size and morphology of these HA nanopowders on the mechanical performance of 45S5 BG scaffolds is evaluated.